The Psychometric Properties of the Stress and Anxiety to Viral Epidemics-6 Items: A Test in the U.S. General Population - Lee, Sangha; Lee, Jihoon; Yoo, Soyoung; Suh, Sooyeon; Chung, Seockhoon; Lee, Sherman A. (Frontiers in Psychiatry, 2021)
Objectives: Many individuals around the world are suffering from psychological distress due to the COVID-19 outbreak. The aim of this study is to explore the validity and reliability of the English version of Stress and Anxiety to Viral Epidemics-6 (SAVE-6), which measures the anxiety response of the general population to the viral epidemic. Methods: A cross-sectional web-based study with self-reporting measures was conducted. A total of 314 United States residents were recruited via online platform in exchange for payment. The participants were asked to an anonymous questionnaire, collecting information on demographics, psychiatric history, SAVE-6, Patient Health Questionnaire-4 (PHQ-4), and the Coronavirus Anxiety Scale. Results: The result from confirmatory factor analysis (CFA) demonstrated that a single-factor model [χ2 (9) = 11.53, p=.24] yielded excellent fit for all of indices [χ2/df ratio=1.28; CFI=1.00; TLI=1.00; SRMR=.02; RMSEA=.03 (.00, .07; 90% CI)] and yielded strong internal consistency reliability (Cronbach’s α=.88). The results from multigroup CFAs showed that there were no gender differences [Δχ2 (6) = 3.20, p=0.78, ns] and no race differences [Δχ2 (6)=3.60, p=0.73, ns] between the models, along with excellent model fits. Conclusions: The results of this study support the reliability and validity of SAVE-6 with strong psychometric properties for the English version of the U.S. population.